2018
DOI: 10.1038/s41397-018-0020-x
|View full text |Cite
|
Sign up to set email alerts
|

The angiotensin-I-converting enzyme insertion/deletion in polymorphic element codes for an AluYa5 RNA that downregulates gene expression

Abstract: Angiotensin-I-converting enzyme (ACE) is involved in the synthesis and degradation of important bioactive peptides. The ACE gene has a 287-bp insertion/deletion polymorphism that controls ACE expression through a mechanism that remains elusive. In this study, we found that the 287-bp polymorphic element of the ACE gene, a member of the AluYa5 sub-family of Alu elements, codes for an RNA molecule that controls the levels of ACE mRNA. Transient transfection of a plasmid containing a CMV promoter upstream of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…The majority of studies included in the present data synthesis analyzed genetic variant rs1799752 located within ACE1 . Even though this polymorphism is intronic, it was shown that the presence of Alu insertion (I allele) correlates with the lower expression of ACE1, possibly via regulation of the transcription rate (Mafra et al, 2018[ 29 ]; Mariner et al, 2008[ 31 ]; Rigat et al, 1990[ 44 ]). The protective effect of the same allelic variant against severe COVID-19 was shown in Spanish and Turkish COVID-19 patients (Aladag et al, 2021[ 4 ]; Gómez et al, 2020[ 20 ]).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies included in the present data synthesis analyzed genetic variant rs1799752 located within ACE1 . Even though this polymorphism is intronic, it was shown that the presence of Alu insertion (I allele) correlates with the lower expression of ACE1, possibly via regulation of the transcription rate (Mafra et al, 2018[ 29 ]; Mariner et al, 2008[ 31 ]; Rigat et al, 1990[ 44 ]). The protective effect of the same allelic variant against severe COVID-19 was shown in Spanish and Turkish COVID-19 patients (Aladag et al, 2021[ 4 ]; Gómez et al, 2020[ 20 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that the Alu is an intron insertion, it can affect gene expression through several mechanisms, including both genetic and epigenetic pathways [60]. At the molecular level, it has also been reported that the presence of the Alu element within intron 16 probably affects the promoter activity of ACE1, which acts as a transacting repressor for RNA polymerase II activity [61,62]. Strikingly, ACE1 levels in the blood are determined by this I/D polymorphism [63].…”
Section: Possible Involvement Of Polymorphic Alu Elements and Their Functional Aspectsmentioning
confidence: 99%
“…Elevated STAT3 also activates PD-L1 in endothelial cells, leading to T-cell lymphopenia [70]. FXIIIB polymorphism AluYa5 insertion has been reported to confer a risk of coronary atherosclerosis [61]. Furthermore, intra-and extracellular FXIIIs are indicated to support the immobilization and killing of bacteria as well as phagocytosis by macrophages, strongly suggesting that FXIII may also function in innate immunity [71].…”
Section: Possible Interplay Between Ace1 and Other Alu Variantsmentioning
confidence: 99%
“…Some polymorphisms in ACE gene are reported to influence the efficacy of these inhibitors among them is the homozygous ACE haplotypes which lead to faster response to ramipril [61]. The expression and function of the ACE itself are affected by its polymorphisms which are associated with susceptibility to different diseases such as hypertension and diabetes mellitus [93]. Notably, polymorphisms in both ACE and ACE2 are important in the regulation of the ACE2 expression [94,95].…”
Section: Vascular Pharmacology 130 (2020) 106680mentioning
confidence: 99%